Maternal self-conception and mental wellbeing during the first wave of the COVID-19 pandemic. A qualitative interview study through the lens of “intensive mothering” and “ideal worker” ideology - Batram-Zantvoort, Stephanie; Wandschneider, Lisa; Niehues, Vera; Razum, Oliver; Miani, Céline (Frontiers in Global Women's Health, 2022)
Mothers tended to be responsible for most of the (additional) caregiving and domestic tasks during the COVID-19 pandemic while simultaneously having to pursue their work duties. Increased role conflicts, parenting stress, and exhaustion predict adverse mental health. We aimed to examine how women referred to and made sense of dominant gender norms in their arrangements of pandemic daily life and how these beliefs impacted their maternal self-conception. Qualitative interviews with 17 women were analyzed through the lens of “intensive mothering” ideology and “ideal workers” norms, emphasizing notions of maternal guilt rising from a perceived mismatch between the ideal and actual maternal self-conception. We found that mothers' notions of guilt and their decreases in health link to dominant discourses on motherhood and intersect with “ideal worker” norms. As such, these norms amplify the burden of gendered health inequalities.